2017
DOI: 10.1213/xaa.0000000000000573
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Pain Management of a Patient Taking Naltrexone HCl/Bupropion HCl (Contrave)

Abstract: A 42-year-old obese woman (body mass index = 30.2 kg/m) presented for urgent anterior cervical diskectomy and fusion. She had been taking oral naltrexone-bupropion extended-release (Contrave, Orexigen Therapeutics Inc, La Jolla, CA) for the past 6 months and continued using it until 12 hours preoperatively. Despite discontinuation of this medication, and employing an intraoperative and postoperative multimodal analgesia strategy, immediate pain control was inadequately achieved. Patients taking opioid antagoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
6
0
2
Order By: Relevance
“…In the large-scale randomized noninferiority cardiovascular outcomes trial that was prematurely discontinued, naltrexone/ bupropion ER resulted in 2.5% (placebo-subtracted) weight loss at 104 weeks (n = 2408 naltrexone/bupropion-treated subjects, n = 2264 placebo-treated subjects) [19]. Interestingly, the reported efficacy in this longer-term study is about half of the reported mean efficacy weight loss reported in the phase III clinical trials of naltrexone/bupropion ER for FDA approval [21]. In the 104 week study, however, MACE was the primary study endpoint, not weight loss [19].…”
Section: Expert Opinionmentioning
confidence: 75%
See 2 more Smart Citations
“…In the large-scale randomized noninferiority cardiovascular outcomes trial that was prematurely discontinued, naltrexone/ bupropion ER resulted in 2.5% (placebo-subtracted) weight loss at 104 weeks (n = 2408 naltrexone/bupropion-treated subjects, n = 2264 placebo-treated subjects) [19]. Interestingly, the reported efficacy in this longer-term study is about half of the reported mean efficacy weight loss reported in the phase III clinical trials of naltrexone/bupropion ER for FDA approval [21]. In the 104 week study, however, MACE was the primary study endpoint, not weight loss [19].…”
Section: Expert Opinionmentioning
confidence: 75%
“…Since FDA approval, only two case reports have reported adverse effects associated with Contrave® [21,22]. The first case was of a 55 year-old obese (BMI 47.75 kg/m 2 ) woman presenting with a body-wide rash with an onset 3 week after initiating Contrave®.…”
Section: Additional Reported Safety Concerns With Naltrexone/bupropiomentioning
confidence: 99%
See 1 more Smart Citation
“…Literatür değerlendirildiğinde, ASDF cerrahisi sonrasında analjezi amacıyla kısıtlı sayıda çalışmanın olduğu görülmektedir. Genellikle postoperatif disfaji, yutkunma ağrısı ve insizyon ağrısını azaltmak amacıyla lokal veya sistemik steroidler, lokal anestezik infiltrasyonu, non-steroid antienflamatuvar ilaç kullanımı veya opioid içeren hasta kontrollü analjezi cihazları veya oral opioid kullanımı ile ilgili çalışmalar bulunmaktadır (16,19) . Analjezik etkinliğe ulaşmak için oranla yüksek dozlarda kullanılan bu medikasyonların iyileşme safhasında akut-subakut dönemde füzyonun yapısına zarar verebileceği veya iyileşmesini uzatabileceği ya da bulantı-kusma gibi olumsuz yan etkileri arttırabileceği, analjezi isterken tam tersine hasta memnuniyetini azaltıcı yan etkilerle karşılaşılabileceği konusunda literatürde farklı çalışmalar bulunmaktadır (16,20) .…”
Section: Güç Analiziunclassified
“…Dosebehovet kan vaere økt mens pasienten fortsatt har sirkulerende naltrekson i blodet, for deretter å bli kraftig redusert ved opphør av antagonisme. En kasuistikk fra 2017 beskriver problematisk postoperativ smertelindring i over ett døgn etter siste inntak av naltrekson/bupropion (5).…”
Section: Gir Uforutsigbarhetunclassified